Berücksichtigen Landwirte bei ihren Investitionsentscheidungen die damit verbundenen Auswirkungen auf die finanzielle Flexibilität ihres Betriebes?; Do Farmers Consider the Effects on Financial Flexibility when Making their Investment Decisions? - Friederike Anastassiadis; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2014)
– for adaption processes which often involve leveraged investments that, in turn, cause decreasing equity capital ratios of farms. It is, therefore, possible that financial flexibility - as the farm's debt capacity - will also decrease. The question arises to what extent decision makers consider the effects on the financial flexibility of the individual farm when making their investment decisions. In the present study, farmers are faced with hypothetical investment alternatives in a discrete choice experiment. The investment alternatives presented to the farmers differ in their profitability, risk and effect on the financial flexibility of the individual farm. The results show that financial flexibility is relevant in their investment decisions. The importance farmers attach to the financial flexibility depends, among others, on their risk attitude and the profitability of the farm.
Keywords: 330